Patient-Centered Care for Patients with Cardiometabolic Diseases: An Integrative Review - Marques, M.C. (2021)
Patient-centered care is essential in high-quality health care, as it leads to beneficial outcomes for patients. The objective of this review is to systematize indicators for the care of patients with cardiometabolic diseases based on patient-centered care, extending from the stages of diagnostic evaluation and care planning to intervention. An integrative literature review was conducted by searching seven scientific databases, and a narrative analysis was performed. A total of 15 articles were included, and indicators related to diagnosis and care planning/intervention were extracted. In the planning of care centered on the person with cardiometabolic diseases, the individuality, dynamics of the processes, flexibility and the participation of all stakeholders should be taken into account. The needs of the person must be addressed through the identification of problems; establishment of individual goals; shared decision making; information and education; systematic feedback; case management; meeting the patient’s preferences and satisfaction with care; engagement of the family; and therapeutic management. The indicators for intervention planning extracted were behavioral interventions, therapeutic management programs, lifestyle promotion, shared decision making, education patient and information, interventions with the use of technology, promotion of self-management, pro